Nutraceuticals for Complementary Treatment of Multisystem Inflammatory Syndrome in Children: A Perspective from Their Use in COVID-19 - Diego Estrada-Luna; Elizabeth Carreón-Torres; Susana González-Reyes; María Fernanda Martínez-Salazar; María Araceli Ortiz-Rodríguez; Esther Ramírez-Moreno; José Arias-Rico; Angélica Saraí Jiménez-Osorio (Life, 2022)
Multisystem inflammatory syndrome in children (MIS-C) has been widely reported in some children diagnosed with SARS-CoV-2. Clinical signs of MIS-C are manifested at 2 to 4 weeks after SARS-CoV-2 infection, where elevated biomarkers of inflammation and cardiac dysfunction are the hallmark of this syndrome when infection or exposure to SARS-CoV-2 has been confirmed. However, after two years of acknowledgment, MIS-C treatment is still under research to reach safety and effectiveness in the acute phase in children. Therefore, in this review, we discuss the potential use of natural compounds with antioxidant and anti-inflammatory effects to reduce collateral damage caused by hyperinflammation in MIS-C pathology for new research in treatment and interventions.